Resistance of cassava genotypes to Vatiga manihotae (Drake 1922) (Hemiptera: Tingidae) - Goncalves da Silva Wengrat, Ana Paula; Barilli, Diandro Ricardo [UNESP]; Uemura-Lima, Daliana Hisako; Gazola, Diego; Bittencourt Guimaraes, Ana Tereza; Pietrowski, Vanda (Soc Brasileira Entomologia, 2020)
Vatiga manihotae (Drake 1922) (Hemiptera: Tingidae) is an important cassava pest due to the great potential damage and the increasing population in recent years. However, few studies about bioecology and control of the cassava lace bug have been conducted and their results don't provide adequate control strategies. An alternative to maintain the population below economic injury levels is through the adoption of host plant resistance. To improve the understanding about the bioecology and find new sources of resistance in cassava, the biological parameters and demographics of V. manihotae on five cassava genotypes (Santa Helena, MEcu 72, Col 22, Clone 02 and Clone 03) under controlled conditions (25 +/- 2 degrees C, 14L/10D) were evaluated. Duration and viability of the stages, the period egg-adult, sex ratio, the pre-oviposition period, fecundity and longevity of male and female was determined, and a fertility life table was prepared. Insects fed on MEcu 72 showed increased nymphal, egg-adult, and pre-oviposition periods and reduced female fecundity and longevity in comparison to the other genotypes. Demographic parameters (Ro, r(m), T, DT) showed a significant impact on the growth potential of V. manihotae fed on MEcu 72 indicating that the populations would diminish over time. The combined effect of these parameters indicated that MEcu 72 has resistance on V. manihotae specimens hindering their development.
Keywords: Cassava pests; Lace bug; Varietal resistance; Biological parameters; Fertility life table